Impacto do enriquecimento de alimentos com ácido fólico na ocorrência de defeitos do tubo neural - Santos, Mara Lúcia Pacheco Lemos dos (2015)
Introduction: Neural Tube Defects (NTD) is a congenital malformation, witch results from the incomplete closure of the neural tube during the fourth week of embryonic development. It is a complex malformation, the second more frequent in the United States of America. It can be prevented by using folic acid (FA) from pre-conception period until the early months of pregnancy. Mandatory flours enrichment with FA occurs in Brazil since 2002. The aim of this study was to evaluate the impact of this action on NTD occurrence, especially on the meningomyelocele sub type, at the Clinical Hospital of the Federal University of Uberlândia (HC-UFU), a regional reference university hospital. Methods: It was a prevalence study, which evaluated all cases of NTDs hospitalized at the Neonatal Unit of HC-UFU, medical records analyze of eight years before until eight years after flours fortification with FA. There were calculated the prevalence of NTD and specially of meningomyelocele subtype at HC-UFU and at Health Region Triângulo do Norte (MRSTN) in pre and post-FA periods. Also, the prevalence ratios were calculated in the same period, with confidence interval of 95% (p<0,05) . Results: A total of 147 cases of NTDs were studied, 81 in the pre-FA period and 66 in the post-FA. Both groups had similar social demographic characteristics. It was detected decreased prevalence of NTD in the Post-FA Group, even in the Neonatal Unit of HC-UFU as in MRSTN, but without statistical significance. The individualized assessment for meningomyelocele sub type showed reduced prevalence, with statistically significant difference. Conclusion: This study showed a reduction in NTD prevalence in the Neonatal Unit of HC-UFU, after the mandatory fortification of flour with folic acid, especially on meningomyelocele.